+0  
 
0
43
1
avatar

( (-sqrt(3)+x)*((1/8)*cos(((5*pi)/3))x(sin(((5*pi)/3))))

 Jun 27, 2021
 #1
avatar+114044 
+1

(    (-sqrt(3)+x)*((1/8)*cos(   ((5*pi)/3)  )x(sin(((5*pi)/3))))

 

I know you have tried your best to put all the brackets in but I am still confused.

Is this what you want.  

 

\((     (-\sqrt{3}+x)   *    (\frac{1}{8}*cos   (\frac{5\pi}{3})    x(sin(\frac{5\pi}{3}))))\\~\\  =(-\sqrt{3}+x)       (\frac{1}{8}*cos   (\frac{5\pi}{3})    x(sin(\frac{5\pi}{3}))\\~\\  =(-\sqrt{3}+x)       (\frac{1}{8}*cos   (\frac{1\pi}{3})    x(-sin(\frac{1\pi}{3}))\\~\\  =(-\sqrt{3}+x)       (\frac{1}{8}*\frac{1}{2}   x(-\frac{\sqrt3}{2}))\\~\\  =(-\sqrt{3}+x)       (-\frac{\sqrt3 x}{32})\\~\\  =\frac{3x-\sqrt3 x^2}{32}\\~\\ \)

 

 

LaTex:

(     (-\sqrt{3}+x)   *    (\frac{1}{8}*cos   (\frac{5\pi}{3})    x(sin(\frac{5\pi}{3}))))\\~\\

 =(-\sqrt{3}+x)       (\frac{1}{8}*cos   (\frac{5\pi}{3})    x(sin(\frac{5\pi}{3}))\\~\\

 =(-\sqrt{3}+x)       (\frac{1}{8}*cos   (\frac{1\pi}{3})    x(-sin(\frac{1\pi}{3}))\\~\\

 =(-\sqrt{3}+x)       (\frac{1}{8}*\frac{1}{2}   x(-\frac{\sqrt3}{2}))\\~\\

 =(-\sqrt{3}+x)        (-\frac{\sqrt3 x}{32})\\~\\

 =\frac{3x-\sqrt3 x^2}{32}\\~\\

 Jun 27, 2021

17 Online Users

avatar
avatar